2019
DOI: 10.3390/vaccines7020043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Recombinant Mouse X Pig Chimeric Anti-Porcine DEC205 Antibody Fused with Structural and Nonstructural Peptides of PRRS Virus

Abstract: Activation of the immune system using antigen targeting to the dendritic cell receptor DEC205 presents great potential in the field of vaccination. The objective of this work was to evaluate the immunogenicity and protectiveness of a recombinant mouse x pig chimeric antibody fused with peptides of structural and nonstructural proteins of porcine respiratory and reproductive syndrome virus (PRRSV) directed to DEC205+ cells. Priming and booster immunizations were performed three weeks apart and administered intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…With a similar approach but using selected peptides from structural and non-structural proteins of PRRSV, Bustamante-Córdova et al. ( 78 ) obtained similar results. More studies are needed to identify if this strategy is suitable for PRRSV in combination with the identification of more immunogenic antigens, better immunization routes, and adjuvant combinations.…”
Section: Vaccinology: a Strategy To Control Prrsvmentioning
confidence: 80%
“…With a similar approach but using selected peptides from structural and non-structural proteins of PRRSV, Bustamante-Córdova et al. ( 78 ) obtained similar results. More studies are needed to identify if this strategy is suitable for PRRSV in combination with the identification of more immunogenic antigens, better immunization routes, and adjuvant combinations.…”
Section: Vaccinology: a Strategy To Control Prrsvmentioning
confidence: 80%
“…In a few studies, minipigs were used as they are regarded as a suitable model when it comes to vaccination through the skin [ 83 ]. It is noted that almost half of the identified papers (n = 57), do not name the pig breed, often referring to it only as commercial breed [ 49 , 51 , 76 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvants are used to enhance and modulate vaccine-induced immunity. Over 60% of identified papers using skin-based vaccination in pigs included adjuvants; the majority mixed or co-inoculated with the vaccine [ 51 , 76 , 88 , 108 , 110 , 112 , 113 , 115 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 129 , 131 , 132 , 133 , 134 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 146 , 151 , 153 , 154 , 156 , 158 , 159 , 160 , 161 , 168 , 179 , 180 , 182 , 186 , 187 , 188 , 196 , 198 , 199 , 201 , 202 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our research group developed a recombinant mouse × pig chimeric antibody against porcine DEC205 receptor (rAb ZH9F7), and antigens from PRRSV were targeted by intradermal application [ 16 , 17 ]. The obtained results showed that the system was immunogenic with limited protective immunity.…”
Section: Introductionmentioning
confidence: 99%